2019
DOI: 10.1038/s41389-019-0175-6
|View full text |Cite
|
Sign up to set email alerts
|

KCTD15 inhibits the Hedgehog pathway in Medulloblastoma cells by increasing protein levels of the oncosuppressor KCASH2

Abstract: Medulloblastoma (MB) is the most common malignant childhood brain tumor. About 30% of all MBs belong to the I molecular subgroup, characterized by constitutive activation of the Sonic Hedgehog (Hh) pathway. The Hh pathway is involved in several fundamental processes during embryogenesis and in adult life and its deregulation may lead to cerebellar tumorigenesis. Indeed, Hh activity must be maintained via a complex network of activating and repressor signals. One of these repressor signals is KCASH2, belonging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…KCTD15 overexpression has never been reported to be linked to pathological states, although it has been indirectly associated with obesity in several literature reports and numerous studies showed an association between this gene and obesity 31,4042 . It is also worth mentioning that the artificial overexpression of KCTD15 inhibits the neural crest formation 37 and that this protein is able to inhibit the Hedgehog pathway in medulloblastoma cells by increasing protein levels of the oncosuppressor KCASH2 43 .…”
Section: Discussionmentioning
confidence: 99%
“…KCTD15 overexpression has never been reported to be linked to pathological states, although it has been indirectly associated with obesity in several literature reports and numerous studies showed an association between this gene and obesity 31,4042 . It is also worth mentioning that the artificial overexpression of KCTD15 inhibits the neural crest formation 37 and that this protein is able to inhibit the Hedgehog pathway in medulloblastoma cells by increasing protein levels of the oncosuppressor KCASH2 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of the Kaplan-Meier plotter analysis determined that the high expression groups of CD44, CCND3, NCALD and MACF1 had an improved prognosis compared with the low expression groups, while KCTD15 exhibited the opposite trend. To the best of our knowledge, KCTD15 upregulation has never been reported to be associated with pathological states, although it has been indirectly associated with several types of cancer, such as pleomorphic adenoma and medulloblastoma ( 39 , 40 ). The specific role of KCTD15 in LUAD should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 95%
“…This is the case of the clade constituted by the highly homologous members KCTD1/KCTD15 [35]. Indeed, these highly homologous proteins play important roles in obesity [32][33][34], cancers [14,36], and scalp-ear-nipple syndrome [30,31]. Although KCTD1/KCTD15 biochemical function is largely unknown, also due to the lack of comprehensive structural data on these proteins [37,38], the above observations prompt for a role in the regulation of some basic process of cell life.…”
Section: Discussionmentioning
confidence: 99%